Genetic Variability, Heritability, Genetic Advance, Correlation, and Path-Coefficient Analysis for Yield Attributing Traits in Chia (Salvia hispanica L.) - Mondal, Upama; Naim, Jannatul; Akter, Sadia; Das, Biswajit; Abdullah, Adrita; Aurin, Fauzia Afrin; Hossain, Mohammad Anwar (Department of Agronomy and Horticulture, IPB University, 2025)
Chia (Salvia hispanica L.) is a promising multifunctional crop renowned for its numerous health benefits. It is essential to comprehend the genetic variability of chia and how various variables impact seed yield to increase its genetic improvement under the agro climatic conditions of Bangladesh. A field experiment was conducted using eight chia genotypes to assess genetic diversity, heritability, and genetic advance (GA), as well as the correlation coefficients for eight factors and their level of association with yield. Analysis of variance results showed significant variation for all the traits, i.e., the number of branches per plant, the number of inflorescences per plant, the length of the main inflorescence, the number of seeds per floret, and seed yield per plant, which differed significantly from one another. GPBC 1, BAU Chia 2, BAU Chia 1, and GPBC 3 were found to be promising genotypes for yield-attributing traits. Higher genotypic and phenotypic coefficient of variation was observed for seed yield per plant and the number of inflorescences per plant. High heritability coupled with high GA% was recorded for the number of inflorescences per plant and seed yield per plant. Seed yield per plant was positively correlated with the number of inflorescences per plant, the length of the main inflorescence, and plant height, while being negatively correlated with days to first flowering and days to maturity. Plant height and the number of inflorescences per plant had the highest direct positive effect on seed yield per plant as revealed through path analysis. The first four principal components contributed 84% of the total variation. The results of the current research may help choose better genotypes and traits for chia breeding initiatives to increase yield.